CONSTRUCTION OF ISOCOMFORTABLE MICROCLIMATE PARAMETERS VALUES MATRIX - R. A. Poddubniy; T. V. Ryabova; A. B. Sulin (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Abstract. In the article is considered the modern approach to the assessment of climate parameters on the basis of the thermal comfort indices in accordance with the requirements of GOST R ISO 7730-2009. For the first time is introduced the concept of isocomfortable values of microclimate parameters, representing a set providing a predetermined thermal comfort level. Are calculated and presented the examples of three-dimensional arrays of given parameters as the convection temperature function from relative humidity and mobility of air. Microclimate parameters ensuring a specified level of thermal comfort were calculated by the method of successive approximations.Proposed in this article matrixes of isocomfortable values of microclimate parameters can be formulated for different combinations of source parameters.